The geomorphology of gnammas (weathering pits) of northwestern Eyre Peninsula, South Australia: typology, influence of haloclasty and origins. Issue 1 (2nd January 2016) - Timms, Brian V.; Rankin, Caleb
ABSTRACT: Gnammas on Eyre Peninsula classify as being either pits, pans or armchair pans. Pit gnammas are relatively deep (depth: diameter > 0.2), usually formed by weathering on a hemispherical front and occur anywhere on a rock outcrop. Subtypes include bowls, canoes, armchair pits and plunge pools: this latter type originate by water evorsion. Pan gnammas occur only on flat surfaces, commencing by horizontal weathering along surface laminations, but further incision is by hemispherical and water-layer weathering. They are shallow petri dish in profile with depth:diameter ratios usually <0.1. Armchair pans initially have similar profiles and origins, but develop further by epigene weathering lowering the slopes and enlarging their catchments and water-layer weathering incising the pans. Removal of weathering products is largely by wind in pans, aided by water overflow in armchair pans, but sediment accumulates in pits, though in the past this was removed by aborigines. Salt weathering is promoted by aerial supply of salt increasing towards the coast so that incision, including attack on western edges, is greatest there. Values of δ (incison:depth ratio) are unique for each population of gnammas and is influenced by haloclasty.